Is failing the key to success? A randomized experiment investigating goal attainment effects on cognitions, emotions, and subsequent performance - Lebeau, J.-C.; Gatten, H.; Perry, I.; Wang, Y.; Sung, S.; Tenenbaum, G. (Psychology of Sport and Exercise, 2018)
Objective: Achieving or failing to achieve a goal impacts our thinking, feeling, and behavior. Grounded in Carver and Scheier's (2003) model on the effect of goal failure on behavioral, affective, and cognitive responses, the present study aimed to uncover the effects of goal success and goal failure on cognitions, emotions, and subsequent performance using a golf putting task. Design and Method: Participants (17 males, 24 females, Mage = 27.17, SDage = 8.91) completed a 24 putt-golf task without the provision of final ball location feedback. Participants were randomly allocated to a goal success or goal failure condition and received a manipulated feedback of their scores to induce goal achievement or goal failure. Self-efficacy was measured every 6 putts, while emotions and executive functions were assessed after the 24th putt. Participants then completed an additional 24 golf putts without any specific goal. Results: Individuals in the goal success condition reported higher self-efficacy, more positive emotions, and less negative emotions than individuals in the goal failure condition. Despite some trends in cognitive and putting performances, non-significant differences were revealed on either of the cognitive tasks or golf putting performances between the goal success and goal failure conditions. Conclusions: Achieving or failing to achieve a goal directly impacts emotions and self-efficacy beliefs, but has a limited effect on subsequent executive functioning and performance on a motor task. The relationship between goal attainment and subsequent performance involves a complex interaction of personal and situational variables.